Metal Support Metal Substrate for Electrochemical Cell
Patent Information
- Application Number
- JP2023555580
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-12
- Filing Date
- 2022-03-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-03-04
AI Technical Summary
Conventional metal substrates for electrochemical cells have pores larger than 10 μm, leading to electrode and electrolyte layer collapse and diffusion of metal components, which compromises the performance and structural integrity of the cells.
A novel metal substrate with a porous metal support and a barrier layer, featuring pores between 3 μm to 75 μm, and a coated barrier layer with micron-sized metal particles and metal oxide particles, to prevent collapse and diffusion, allowing for high power density and mechanical strength.
The solution enables the production of thin, lightweight electrochemical cells with high power density, exceeding 1,000 W/kg, and maintains a flat, defect-free surface, suitable for applications in aerospace, defense, and energy sectors.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] Rights enjoyed by the government This invention was made with the support of the National Aeronautics and Space Administration under Contract No. 80NSSC19C0577 and the United States Government. The United States Government has rights to certain patents relating to this invention.
[0002] Related Applications This application claims the benefit of U.S. Provisional Patent Application No. 63 / 160,187, filed March 12, 2021, the contents of which are incorporated herein by reference.
[0003] The present invention relates to metal substrates for use in metal-supported electrochemical cells. The present invention also relates to methods for fabricating metal substrates and metal-supported electrochemical cells fabricated by the methods. All components described herein are useful, for example, in the fabrication and operation of solid oxide fuel cells (SOFCs), solid oxide electrolysis cells (SOECs), or solid oxide electrochemical sensors. [Background technology]
[0004] An electrochemical cell is composed of three essential elements, an oxygen electrode, an electrolyte, and a fuel electrode, which are arranged in layers. In particular, in a solid oxide fuel cell (SOFC), the oxygen electrode functions to reduce oxygen molecules to oxide ions by an electron source. The electrolyte functions as a medium to transport the oxide ions from the oxygen electrode to the fuel electrode. The fuel electrode functions to oxidize fuel feeds such as hydrogen and carbon monoxide by the oxide ions to produce water and carbon dioxide, as well as electrons. Methane is another suitable fuel feed. Multiple fuel electrodes are connected to an external electric circuit, and the electrons generated by the fuel electrode are transferred to the oxygen electrode through the external electric circuit to generate electricity. Since the voltage obtained from a single electrochemical cell is usually low, multiple electrochemical cells are connected in series or parallel to form a high-power electrochemical cell stack.
[0005] Electrochemical cells are structurally supported and physically strengthened by porous substrates that hold either the fuel electrode, electrolyte, or oxygen electrode. Various substrate materials have been proposed as suitable porous metal substrates for improving the performance of electrochemical cells. Powder metallurgy techniques can be used to prepare porous metal substrates with various types and sizes of pores. Conventional metal substrates have pores that are typically in the range of more than 10 μm, but the pore sizes are larger than the grain sizes of conventional fuel electrode and electrolyte materials, which are typically in the submicron range. In addition, the pore sizes of conventional metal substrates are larger than the normal layer thicknesses of the respective fuel electrode and electrolyte layers, resulting in the following defects:
[0006] Those skilled in the art will recognize that the pore size of the metal substrate plays an important role in avoiding defects during cell fabrication and operation. Substrates with large pore sizes, greater than 10 μm in diameter, are prone to collapse and crumbling of the electrode and electrolyte layers and detrimental diffusion of the metal components of the electrode and electrolyte layers into the substrate. As an example, chromium in the ferrite substrate can diffuse into the nickel / yttria stabilized zirconia (Ni-YSZ) anode under operating conditions, forming detrimental nickel-chromium alloys. Nickel in the anode can also diffuse into the substrate, forming detrimental alloys. Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention is to maintain the pore size of the metal substrate in the range of less than 10 μm and to form pores in the metal substrate having a size smaller than the particle size (particle size) of conventional fuel electrodes and electrolyte materials formed on the metal substrate. It is necessary to reduce the pore size of the metal substrate from the normal layer thickness (5 μm to 20 μm) of each fuel electrode and electrolyte layer. Unfortunately, it is extremely difficult to realize a metal substrate with pores less than 10 μm, which requires highly reliable manufacturing technology.
[0008] The desired standard power per unit weight for a high performance fuel cell is to achieve a high power density of about 1,000 W / kg, preferably more than about 2,000 W / kg. A fuel cell that achieves high power density is one that can deliver a current per unit area of about 1 A / cm while maintaining a cell substrate with sufficient mechanical strength and thickness and a lightweight structure. 2 It is necessary to operate at current densities exceeding
[0009] It is desirable to produce improved porous metal substrates for electrochemical cells that are thin, lightweight, and formed into a monolithic structure to retain optimized power density. Desirable are porous metal substrates that are substantially flat and free of flaws with thicknesses of less than about 1.0 mm, and preferably less than about 0.5 mm, and that can be fabricated to planar areas of up to about 10 cm x 10 cm or more, depending on the intended application. Most desirable are porous metal substrates that are resistant to pressed electrode molding and resistant to diffusion of electrode-electrolyte components into the substrate. [Means for solving the problem]
[0010] The present invention aims to provide a metal substrate for a metal supported electrochemical cell which overcomes the drawbacks of electrode layer collapse in large pore metal substrates and the difficulties in manufacturing small pore metal substrates by incorporating a novel barrier layer as part of the electrochemical cell. Accordingly, one embodiment of the present invention provides a novel metal substrate for use in a metal supported electrochemical cell comprising:
[0011] (a) a porous metal support having a first metal and forming a layer having pores in a particle size range of about 3 μm to 75 μm;
[0012] (b) a barrier layer coated on one side of the porous metal support and comprising micron-sized particles of a second metal and micron-sized particulates of a metal oxide.
[0013] Another embodiment of the present invention provides a method for making a novel metal substrate for use in a metal supported electrochemical cell comprising: (a) providing a metal support;
[0014] (a) coating one side of a porous metal support comprising a first metal forming a layer having pores in the size range of about 3 μm to 75 μm with an ink barrier layer comprising a solvent, a binder, micron-sized particles comprising a second metal, and metal oxide particulates of submicron size to form a green substrate composite;
[0015] (b) heating the green substrate composite under conditions sufficient to form a metal substrate comprising a porous metal support comprising a first metal forming a layer having pores in the size range of about 3 μm to 75 μm, thereby coating one side of the metal substrate with a barrier layer comprising micron sized particles of a second metal and submicron sized metal oxide particulates.
[0016] Yet another embodiment of the present invention provides a novel metal supported electrode comprising the following components (a)(i), (a)(ii) and (b) arranged in layers:
[0017] (a)(i) a porous metal support comprising a first metal forming a layer having pores in the size range of about 3 μm to 75 μm; (a) a metal substrate, and (a)(ii) a barrier layer coated on one side of the porous metal support and comprising micron-sized particles of a second metal and micron-sized particles of a metal oxide.
[0018] (b) an electrode layer disposed on the barrier layer;
[0019] Yet another embodiment of the present invention provides a method for producing a metal supported electrode, comprising the steps of: (a) preparing a metal supported electrode;
[0020] (a) coating one side of a layer of porous metal support comprising a first metal having pores in the size range of about 3 μm to 75 μm with an ink barrier layer forming a green substrate composite comprising a solvent, a binder, micron-sized particles comprising a second metal, and micron-sized particulates of a metal oxide;
[0021] (b) coating the green substrate composite with an electrode ink comprising a solvent, a binder, and electrode material particles to form a green electrode composite; and
[0022] (c) heating the bare-electrode composite under conditions sufficient to form a metallic supporting electrode.
[0023] Yet another embodiment of the present invention provides a novel metal support electrochemical cell comprising the following components (a), (b), (c) and (d) arranged in layers:
[0024] (a) a metal substrate having the following configuration: (a)(i) a porous metal support comprising a first metal forming a layer having pores in the size range of about 3 μm to 75 μm; and (a)(ii) a barrier layer comprising micron-sized particles of a second metal and micron-sized particles of a metal oxide, coated on one side of the metal substrate;
[0025] (b) a first electrode layer disposed on the barrier layer;
[0026] (c) an electrolyte layer disposed on the first electrode layer;
[0027] (d) a second electrode layer disposed on the electrolyte layer and having an opposite polarity to the first electrode layer.
[0028] The present invention provides a novel porous metal substrate and a novel method for its manufacture that is useful for metal-supported electrochemical cells, such as metal-supported solid oxide fuel cells (MS-SOFCs) or solid oxide electrolysis cells (SOECs) or solid oxide electrochemical sensors. The present invention is advantageous in that it allows the manufacture of cells with a substantially flat and flawless layer surface having a planar area of up to about 10 cm x 10 cm or more, and a substrate thickness of less than about 1.0 mm, preferably about 0.1 mm to 0.50 mm. The technical condition of minimizing the cell thickness while maintaining a substantially flat and flawless layer surface is important for achieving light weight and high power density of cells with power per unit weight of about 1,000 W / kg, preferably more than about 2,000 W / kg.
[0029] The fabrication process for metal supported solid oxide cells (MS-SOC) is completed by screen printing the cell component layers, followed by degreasing and sintering. The ink barrier layer formulation selected based on the criteria described below significantly suppresses, but does not completely eliminate, the collapse and diffusion of the cell components due to the large pore size of the porous metal support. The selection of a novel barrier layer that constitutes the resulting bimodal distribution of micron-type particles and micron-type fine particles fills the gaps and pores of the metal support in the particle size range of about 3 μm to 75 μm. The overall process described herein is a novel process of the present invention for producing high current density thin substrates generating high power density solid oxide cells exceeding about 1,000 W / kg.
[0030] The implementation of novel metal supported solid oxide fuel cells (MS-SOFC) offers the opportunity to deploy high power density, fast response, durable fuel cell generators for many applications, including aerospace, defense, and energy sector applications. The metal supported electrochemical cells of the present invention allow the design of lighter weight, thermally efficient, efficient, and durable electrochemical cell stacks. [Brief description of the drawings]
[0031] [Figure 1] FIG. 1 is a cross-sectional view of an electrochemical cell having an anode supported on a substrate having a porous metal support coated with a barrier layer.
[0032] [Diagram 2] Graph showing polarization curve characteristics (current density I vs. voltage V and current density vs. power P) during operation of a metal supported solid oxide fuel cell according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] For purposes of the present invention, the term "particles" refers to small size crystallites or particles of various and random distribution as described herein.
[0034] The term "layer" as used herein refers to a quasi-two-dimensional (thin film-like) structure in which the length and width dimensions are significantly greater than the thickness dimensions. A layer can be considered as a plane or thin plate of one thickness of a first material covering all or a portion of the surface of a second material. The term "layer" as used herein does not limit a layer to a particular shape, for example, a layer can be given a square, rectangle, hexagon, circle, oval, or any other shape selected by the design. All layers in cells that usually have the same shape can be aligned, sealed, and secured at the edges or corners.
[0035] The term "about" in any numerical range described herein refers to the lower limit of the numerical range. Unless otherwise limited, the term "about" is intended to refer to both the lower and upper limits of the numerical range, taking into account the permissible variance of both limits.
[0036] A technical advantage of the present invention resides in producing a substantially planar substrate layer and an electrode layer disposed thereon in a strong and adherent manner. The term "planar" refers to a flat surface characterized by a line or contour path that is substantially free of irregularities or undulations. Acceptable standards for flatness are determined by visual inspection using an optical microscope at no magnification or at a magnification of about 10-20 to look for warping or deformation of the surface.
[0037] Another technical advantage of the present invention is the production of a substrate layer that is substantially free of surface defects, such that the substrate layer does not have an unacceptable number of cracks, hairs, pinholes, or other imperfections that affect surface uniformity. As with inspection of the substrate layer for warpage, imperfections can be identified by visual inspection without magnification of the exposed surface of the substrate layer or other cell layers. Alternatively, the desired surface can be visually inspected with an optical microscope at approximately 10-20x magnification. It is particularly beneficial to inspect the half-cell, including the porous metal support, barrier layer, fuel electrode, and electrolyte, prior to application of the cathode layer.
[0038] It is yet another technical advantage of the present invention to produce a thin, lightweight substrate as described herein as a composite comprising a porous metal support and a barrier layer. The substrate of the present invention is advantageous in that it has a thickness of less than about 1.1 mm, typically from about 100 μm to about 1,000 μm.
[0039] In one exemplary embodiment, the novel metal substrate for use in a metal supported electrochemical cell comprises the following components (a), (b) and a barrier layer:
[0040] (a) a layered porous metal support, the layered porous metal support being formed of a first metal selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof, and having pores in the size range of about 3 μm to 75 μm; and
[0041] (b) a barrier layer coated on one side of the porous metal support and comprising micron size range particles of about 2 μm to 20 μm formed of a second metal selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof; The barrier layer further contains metal oxide particulates in the submicron particle size range of about 0.1 μm to less than 1 μm, comprising a third metal selected from the group consisting of cerium, gadolinium, samarium, lanthanum, yttrium, chromium, titanium, calcium, strontium, iron, nickel, cobalt, aluminum, manganese, and mixtures thereof.
[0042] In another exemplary embodiment of the present invention, the layer thickness of the porous metal support has a grain size range of about 80 μm to 1,000 μm and a porosity of greater than about 20% by volume, with a preferred embodiment having a porosity in the range of about 25% to 50% by volume.
[0043] In another exemplary embodiment of the present invention, the porous metal support layer comprises a ferritic alloy, preferably comprising greater than about 15 weight percent chromium.
[0044] The barrier layer in another exemplary embodiment of the present invention has a thickness in the grain size range of about 10 μm to 50 μm.
[0045] In another exemplary embodiment of the present invention, the barrier layer comprises micron-sized particles of a second metal selected from the group consisting of nickel and copper. In another exemplary embodiment, the barrier layer comprises submicron-sized metal oxide particulates of ceria or rare earth doped ceria. In another exemplary embodiment, the barrier layer comprises submicron-sized metal oxide particulates of lanthanum chromate or rare earth doped lanthanum chromate. In yet another exemplary embodiment, the barrier layer comprises submicron-sized metal oxide particulates of strontium titanate or rare earth doped strontium titanate.
[0046] In yet another exemplary embodiment, the present invention comprises the following, arranged in layers: (a) a polymerizable composition comprising: a polymerizable polymer having a polymerizable functional group;
[0047] (a) a metal substrate comprising: (a)(i) and (a)(ii) (a)(i) a porous metal support forming a single layer and comprising a first metal selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof and having pores in the size range of about 3 μm to 75 μm; (a)(ii) a barrier layer comprising micron-sized particles of a second metal selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof coated on one side of the porous metal support and having a particle size range of about 2 μm to 20 μm; and (b) an electrode layer disposed on the barrier layer; The barrier layer further comprises micron-sized particles of a metal oxide comprising a third metal selected from the group consisting of cerium, gadolinium, samarium, lanthanum, yttrium, chromium, titanium, calcium, strontium, iron, nickel, cobalt, aluminum, manganese, and mixtures thereof, having a particle size range of about 0.1 μm to less than 1 μm.
[0048] A layered metal supporting electrode is provided.
[0049] In yet another exemplary embodiment, the present invention provides a novel metal support electrochemical cell comprising the following components arranged in layers: (a), (b), (c) and (d):
[0050] (a) A metal substrate having (a)(i) and (a)(ii). (a)(i) a porous metal support comprising a first metal forming a layer selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese, and mixtures thereof, and having pores in the size range of about 3 μm to 75 μm; (a)(ii) a barrier layer coated on one side of a porous metal support and comprising micron-sized particles of a second metal selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof having a particle size range of about 2 μm to 20 μm and a metal oxide having a particle size range of about 0.1 μm to 1 μm and comprising a third metal selected from the group consisting of cerium, gadolinium, samarium, lanthanum, yttrium, chromium, titanium, calcium, strontium, iron, nickel, cobalt, aluminum, manganese and mixtures thereof;
[0051] (b) a first electrode layer formed on the barrier layer;
[0052] (c) an electrolyte layer disposed on the first electrode layer;
[0053] (d) a second electrode layer disposed on the electrolyte layer and having an opposite polarity to the first electrode layer.
[0054] The electrochemical cell of yet another exemplary embodiment of the present invention is a metal-supported solid oxide fuel cell or a metal-supported solid oxide electrolysis cell in which the first electrode layer is a fuel electrode layer and the second electrode layer is an oxygen electrode layer (or an air cathode layer). The electrochemical cell of another exemplary embodiment of the present invention has a fuel electrode layer having a thickness of about 3 μm to 20 μm, an electrolyte layer having a thickness of about 1 μm to 20 μm, and an oxygen electrode layer having a thickness of about 10 μm to 30 μm.
[0055] In another exemplary embodiment, the fuel electrode layer is a composite comprising nickel or nickel oxide in combination with a metal oxide selected from the group consisting of zirconium, yttrium, cerium, scandium, gadolinium, samarium, calcium, lanthanum, strontium, magnesium, gallium, barium oxides and mixtures thereof. In one preferred embodiment, the fuel electrode layer is nickel oxide-yttria stabilized zirconia (NiO-YSZ).
[0056] In yet another exemplary embodiment, the electrolyte layer comprises a metal oxide selected from the group consisting of oxides of zirconium, yttrium, cerium, scandium, gadolinium, samarium, lanthanum, strontium, magnesium, gallium, barium, calcium, and mixtures thereof. In one preferred embodiment, the electrolyte layer is yttria stabilized zirconia.
[0057] In yet another exemplary embodiment, the oxygen electrode layer is selected from a composition represented by the formula ABO3, where A is a material selected from the group consisting of barium, strontium, lanthanum, samarium, praseodymium, and combinations thereof, and B is a material selected from the group consisting of iron, cobalt, nickel, and manganese, and in a preferred embodiment, ABO3 is lanthanum strontium cobalt ferrite (LaSrCoFeO3).
[0058] In another exemplary embodiment of the electrochemical cell, the intermediate layer between the electrolyte layer and the oxygen electrode layer may have a thickness of about 1 μm to 20 μm. The intermediate layer has a function of retarding the reaction between the electrolyte material and the oxygen (or cathode) material. The intermediate layer typically comprises one or more rare earth elements doped with one or more metals selected from the group IIA elements. In one embodiment of the invention, the one or more rare earth elements are selected from the group consisting of lanthanum, samarium, yttrium, gadolinium, and combinations thereof. In one embodiment, the intermediate layer is compounded with ceria.
[0059] To aid in understanding the present invention, a cross-sectional view of an electrochemical cell according to one embodiment contemplated by the present invention is shown in Figure 1. Those skilled in the art will recognize that the electrochemical cell includes at least five layers, in this order from bottom to top: a porous metal support, a barrier layer, a fuel electrode (anode), an electrolyte, and an oxygen electrode (cathode). In the present invention, a barrier layer of a specific chemical composition is disposed between the fuel electrode and a porous metal support of a specific pore size.
[0060] Porous metal supports typically include any metallic material that has the strength, electrical conductivity, and thermal expansion coefficient that can be used in electrochemical cells. Porous metal supports are typically used as pure metallic elements or combined metallic elements such as alloys. Non-limiting examples of metal supports suitable for the present invention include ferritic alloys that contain iron as the main component, chromium in an amount of more than 15% by weight, and small amounts of other metallic elements. Porous metal supports are typically formed in a thin plate or layer having a layer thickness range of about 80 μm (0.08 mm) to 1,000 μm (1 mm), preferably about 100 μm (0.1 mm) to 500 μm (0.5 mm). All metal supports and "porous" metal supports that have multiple pores, grooves, and / or communicating holes formed within the metal support to facilitate the diffusion of gas components are necessary and important. The porosity range is typically greater than 20 volume (vol) % with respect to the total volume of the porous metal support, and is preferably about 25 to 50 volume %.
[0061] A porous metal support in the form of a thin plate or layer with a layer thickness in the upper range (800-1,000 μm) can be purchased from a supplier. A porous metal support with a layer thickness of less than about 500 μm can be manufactured by a tape casting method known in the art (a thin film formation method in which a material powder suspension is cast into a thin film, dried, and sintered). The tape casting method includes the steps of preparing a suspension that typically includes a solvent, a binder, a powdered metal element, an alloy or a precursor thereof, a pore former, and optionally at least one of a plasticizer and a dispersant, and casting the suspension into a thin plate or film of the desired thickness. The solvent is then removed to form a dough, which is then exposed to an oxidizing atmosphere air at a temperature of about 300° C. to 800° C. through a debinding step or a baking step. The dough is then further heated in a reducing atmosphere, such as a mixture of hydrogen and an inert gas such as argon or nitrogen, to form a metal support of a denser porous material. For example, US Patent Application Publication No. 2008 / 0096079, which is incorporated herein by reference, describes the preparation of thin layer porous metal supports from metal powders.
[0062] The micron-sized particles of the second metal in the barrier layer are typically obtained from a metal of acceptable electrical conductivity for the given electrode layer coated on the barrier layer. The second metal is typically selected from metals identical or nearly identical to the electronically conductive metal in the selected electrode to reduce the electrical resistance between the barrier layer and the electrode. In one embodiment of the present invention, the second metal in the barrier layer is selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese, and mixtures thereof. In particular, nickel is one example of a preferred second metal. The micron-sized particles of the second metal in the barrier layer function to fill gaps in the porous metal support and along the interface between the barrier layer and the porous metal support.
[0063] The micron-sized particles of metal oxide in the barrier layer have the appropriate porosity and oxide ions (O 2) conductivity. In one embodiment of the present invention, the metal oxide of the micron-sized particulate is formed from a third metal selected from the group consisting of cerium, gadolinium, samarium, lanthanum, yttrium, chromium, titanium, calcium, strontium, iron, nickel, cobalt, aluminum, manganese, and mixtures thereof. The metal oxide is compatible with various embodiments of the present invention. In one exemplary embodiment, the metal oxide of the barrier layer is ceria or rare earth doped ceria. In another exemplary embodiment, the metal oxide of the barrier layer is lanthanum chromite or rare earth doped lanthanum chromite. In yet another exemplary embodiment, the metal oxide of the barrier layer is strontium titanate or rare earth doped strontium titanate. The submicron-sized particulates, which function to fill the gaps between the micron-sized particles, form particularly uniform, flat, and flawless surfaces at the interface between the barrier layer and the metal support on one side and the interface between the barrier layer and the electrode on the other side.
[0064] In preparing the substrate of the present invention, the porous metal support is first coated with an ink barrier layer comprising a solvent, a binder, micron-sized powder particles of a second metal, and submicron-sized powder particles of a metal oxide. The ink barrier layer also typically comprises a plasticizer, a dispersant, or a mixture thereof. For example, micron-sized particles of the selected second metal or elemental or oxide form of nickel or an oxide such as nickel oxide are typically included in the ink barrier layer. The micron-sized particles incorporated in the ink barrier layer typically range in size from about 1 μm to 10 μm. The micron-sized particles content in the ink barrier layer typically ranges from about 34% to 65% by weight based on the total weight of the metals included in the ink barrier layer. The micron-sized particles incorporated in the ink barrier layer as the selected metal oxide particles typically range in size from about 0.05 μm to 0.5 μm. The micron-sized particles in the ink barrier layer typically range in size from about 35% to 66% by weight based on the total weight of the metal content in the ink barrier layer.
[0065] The solvent used in the ink barrier layer is selected from common organic solvents that are easily removable at temperatures of about 50° C. to 120° C. and is typically selected from the group consisting of alcohols, esters, and ketones. The amount of solvent is typically about 5% to 20% by weight based on the total weight of the ink barrier layer. The amount of binder is typically selected from commercially available binder formulations, such as alcohol and polyvinyl binders, at about 5% to 20% by weight. The amount of suitable plasticizers, including phthalates and glycols, is typically about 1% to 10% by weight. Suitable dispersants include fish oil and amine groups, which are typically present in amounts of about 1% to 10% by weight. After all components are mixed, the ink barrier layer is screen printed on one side of the porous metal support to produce a green substrate composite.
[0066] After printing the ink barrier layer, the green substrate composite is degreased and sintered in a two-stage heat treatment to produce the porous metal substrate of the present invention. The first stage heat treatment is performed in air flow. The substrate-ink composite is heated to a temperature range of about 60°C to 450°C to perform the first stage heat treatment. The second stage is heated to a temperature range of about 900°C to 1400°C in an atmosphere of a reducing mixture of inert gas such as helium, nitrogen, argon, and hydrogen to form and adhere the barrier layer to the porous metal substrate, and sinter the green substrate. The barrier layer has the advantage of preventing the embedding of cell components into the pores of the metal substrate, as well as preventing harmful diffusion of the substrate components to the electrodes. Nevertheless, due to the porosity of the metal substrate and the barrier layer, gas components diffuse in and out of the substrate. In addition, the barrier layer components are selected to sufficiently correspond to the values of electrical conductivity, oxide ion conductivity, and thermal expansion coefficient of the electrode to be covered by the barrier layer.
[0067] Useful materials for the fuel and oxygen electrodes should have stability at operating temperatures, a coefficient of thermal expansion compatible with that of the solid oxide electrolyte, and chemical compatibility with the solid oxide electrolyte and other materials during fabrication and operation of the solid oxide cell. In forward operation, the function of the fuel electrode is to combine oxide ions diffusing through the electrolyte with fuel supplied to the fuel electrode to produce electron flow and water and carbon dioxide.
[0068] Those skilled in the art should understand that the present invention should not be limited to any particular fuel electrode, electrolyte or oxygen electrode. While the present invention can be applied to any fuel electrode, electrolyte or oxygen electrode known in the art, the fuel electrode is typically composed of a porous inorganic-metal composite (cermet) layer that allows the diffusion of the fuel, usually a gaseous reformate containing hydrogen and carbon monoxide, into the electrode. Fuel electrodes that require electrical and ionic conductivity are typically composed of inorganic-metal composites (cermets) that combine inorganic and metallic materials produced by standard ceramic processing techniques. Suitable fuel electrode layers are, for example, composed of nickel or nickel oxide and a metal oxide selected from the group consisting of zirconium, yttrium, cerium, scandium, gadolinium, samarium, calcium, lanthanum, strontium, magnesium, gallium, barium oxides and mixtures thereof. In one embodiment of the present invention, the fuel electrode layer is composed of nickel oxide-yttria stabilized zirconia (NiO-YSZ).
[0069] Solid oxide electrolytes contain oxide ions (O 2 The electrolyte is typically comprised of a dense ceramic layer that conducts ions (ions). The electrolyte is typically comprised of a metal oxide selected from the group consisting of scandium, cerium, zirconium, lanthanum, strontium, magnesium, gallium, barium, yttrium, gadolinium, samarium, calcium, and mixtures thereof. Examples of materials that form the solid oxide electrolyte layer include yttria stabilized zirconia (YSZ) and scandia stabilized zirconia (ScSZ). The new electrolyte developed improves the oxide ion conductivity and reduces the problems of stiffer materials and resistivity, improving the electrolyte layer performance utilized in the present invention.
[0070] The oxygen electrode provides a uniform flow of oxygen across the electrode and oxide ions (O 2The oxygen electrode must be porous enough to conduct the oxygen to the solid oxide electrolyte. Non-limiting examples of materials that can form the oxygen electrode include lanthanum strontium manganite (LSM), lanthanum strontium ferrite (LSF), (La,Sr)(Co,Fe)O3, and cobaltite.
[0071] The fuel electrode layer, electrolyte layer and oxygen electrode layer are formed by screen printing and heat treatment of respective inks. The inks used typically contain a solvent, a binder, the ceramic material and metal components of the particular layer concerned, and optionally at least one plasticizer and dispersant. The ink for the fuel electrode layer of an exemplary embodiment of the present invention includes a solvent, an inorganic-metal composite powder precursor of the fuel electrode layer, a binder, a plasticizer and a dispersant. After sufficient mixing, the fuel electrode ink is screen printed onto the barrier layer and dried at a temperature of about 60°C to 120°C. The electrolyte ink is then screen printed onto the fuel electrode layer. The multi-layer composite including the porous metal support, the barrier layer, the printed fuel electrode layer and the printed electrolyte layer is heat treated first with heated air and then in a reducing atmosphere as described above to form the metal supported half-cell. The sintering temperature range for the electrolyte layer and the anode layer is typically up to 1400°C. After sintering, the oxygen electrode ink is screen printed onto the electrolyte layer to form the oxygen electrode layer.
[0072] Under normal operating conditions, each electrochemical cell generates only a low voltage power of less than about 1 V, but many applications require high voltage, so in practical applications, multiple electrochemical cells of the present invention can be connected in series or parallel to form a stack to obtain a high voltage that meets the application. The stack is formed by fixing each electrochemical cell between two connection terminals that provide mechanical strength to the stack and separate the cells from each other.
[0073] Since the connection terminals are exposed to high temperatures on both the oxidation and reduction sides of the cell, and must retain stable properties of non-deterioration, the connection terminals are made of a conductive material that is resistant to the heat and chemical environments to which they are exposed. The connection terminals of one embodiment of the present invention are made of a metal plate or foil of, for example, a high-temperature resistant stainless steel alloy. In another embodiment, the connection terminals are made of an inorganic-metal composite material that has acceptable thermal stability and electrical conductivity. The present invention is not limited to a specific connection terminal material or layer thickness of the connection terminal layer. Working Example
[0074] In this example, a metal substrate with a porous metal support and a barrier layer was formed using ferrite metal powder by the manufacturing method of the present invention. Ferrite metal powder (iron-chromium alloy, average particle size 10 μm) and polymethylmethacrylate (average particle size 8 μm) pore former were mixed with a commercially available blend of solvent, binder and plasticizer, and the resulting mixture was cast by tape casting. The casted green film was heat-treated in air to degrease the organic material, and then sintered in a mixed gas atmosphere of hydrogen and inert gas to form a porous metal support with a thickness of 0.45 mm (450 μm) and an average pore size of 10 μm.
[0075] An ink barrier layer containing a solvent (alcohol), polyvinyl binder (6 g), phthalate plasticizer (1 g), dispersant (fish oil, 1 g), micron-sized nickel particles (30 g, 5 μm), and submicron-sized gadolinium particle-doped ceria (20 g, 0.05 μm, 10% gadolinium) was screen-printed onto a porous metal support to produce a green substrate composite.
[0076] A fabric fuel electrode composite was prepared by screen printing a fuel electrode (anode) ink containing alcohol (6 g), polyvinyl binder (6 g), phthalate plasticizer (1 g), dispersant (fish oil, 1 g), nickel oxide (30 g), and yttria-stabilized zirconia (20 g) onto the fabric substrate composite.
[0077] An electrolyte ink containing alcohol (10 g), polyvinyl binder (6 g), phthalate plasticizer (2 g), fish oil dispersant (2 g), and scandium-stabilized zirconia (50 g) was screen printed onto the fabric fuel electrode composite to form a fabric half-cell.
[0078] The resulting dough half-cells were co-sintered by the following heating procedure: The dough half-cells were placed in air at room temperature and heated to a temperature of 400°C, and then held at this temperature for 1-5 hours. Next, the hydrogen (5% by volume) mixed inert gas atmosphere in which the samples were placed was heated to a temperature of 1320°C and held for 1-5 hours, after which the samples were cooled under a flow of hydrogen in the inert gas.
[0079] The sintered half-cells were observed under a scanning electron microscope (SEM). Energy dispersive X-ray spectroscopy (EDS) spectra confirmed the fabrication of the metal-supported solid oxide half-cell with well-defined boundaries (interfaces) between adjacent layers of the half-cell including the porous metal support, barrier layer, fuel electrode (anode), and electrolyte. A flat and uniform surface of the top electrolyte layer was observed without any warping or defects. Oxygen electrode coverage and fuel cell performance testing showed the overall acceptability of the half-cell structure.
[0080] The formed metal-supported half-cell was used to fabricate a metal-supported solid oxide fuel cell (MS-SOFC) and perform cell performance testing. A bare oxygen electrode layer containing lanthanum cobalt-ceria based material (LaSrCoFeO3) was coated onto the electrolyte layer of the half-cell by screen printing. The half-cell was sintered by the above procedure to form a metal-supported solid oxide fuel cell (11 μm, 0.8 mm thick).
[0081] 2 shows the polarization characteristic curves, i.e., current I vs. voltage V and current I vs. power P, based on the test results of a metal-supported solid oxide fuel cell. The test results show an open circuit voltage (OCV) at 750° C. of slightly more than 1.10 V and a current density of essentially 1 A / cm 2 The nominal cell current density in FIG. 2 is 0.7 A / cm 2 and generated 8 watts of power (active area 4 × 4 cm2 Cell area 5×5cm 2 Peak power of the cell is 1A / cm 2 was calculated to be 12 watts, equivalent to a cell specific power of 1,000 W / kg.
[0082] Based on the results of fabricating 0.8 mm thick cells, assuming the same cell performance, the thinner metal-supported solid oxide fuel cells (7 g, 0.45 mm cell thickness) and the even thinner metal-supported solid oxide fuel cells (4.5 g, 0.27 mm cell thickness) showed a significant improvement in the specific cell power. For example, the power generated from a single cell of 12 W (active area 4 × 4 cm) was 1.2 W at 0.45 mm vs. 0.27 mm cell thickness. 2 Cell area 5×5cm 2 The cell specific powers in the cases of (a) and (b) are approximately 1700 W / kg and approximately 2600 W / kg, respectively.
[0083] Although a limited number of embodiments of the present invention have been described in detail, it should be readily understood that the present invention should not be construed as being limited to the disclosed embodiments. Rather, the present invention can be modified without description to include any number of variations, modifications, substitutions, or equivalent arrangements commensurate with the spirit and scope of the present invention. It should also be understood that aspects of the various embodiments of the present invention described may include only some of the described embodiments. Accordingly, the present invention should not be limited by the foregoing description, but should be limited only by the scope of the appended claims.
Claims
1. (a) a porous metal support having pores in the pore size range of 3 μm to 75 μm and forming a layer comprising a first metal; (b) a barrier layer comprising micron-sized particles of a second metal and micron-sized particulate metal oxide on one side of the porous metal support, said barrier layer being suitable for use in a metal support electrochemical cell.
2. 2. The metal substrate of claim 1, wherein the porous metal support layer has a layer thickness in the range of 80 μm to 1,000 μm and a porosity in the range of 25% to 50% by volume.
3. 10. The metal substrate of claim 1, wherein the porous metal support layer comprises a ferritic alloy containing greater than 15 mole percent chromium.
4. 2. The metal substrate according to claim 1, wherein the barrier layer has a layer thickness in the range of 10 μm to 50 μm.
5. the micron-type particles of the second metal have a particle size in the range 2 μm to 20 μm; 2. The metal substrate of claim 1, wherein the second metal is selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof.
6. Micron-type particulate metal oxides have particle sizes in the range of 0.1 μm or more and less than 1 μm; 10. The metal substrate of claim 1, wherein the metal oxide comprises a third metal selected from the group consisting of cerium, gadolinium, samarium, lanthanum, yttrium, chromium, titanium, calcium, strontium, iron, nickel, cobalt, aluminum, manganese, and mixtures thereof.
7. The micron-sized particles include nickel, 2. The metal substrate of claim 1, wherein the micron-sized fine particles of the metal oxide include ceria or rare earth-doped ceria, lanthanum chromite or rare earth-doped lanthanum chromite, or strontium titanate or rare earth-doped strontium titanate.
8. (a) providing a porous metal support having pores in the pore size range of 3 μm to 75 μm and formed as a layer comprising a first metal, and coating one side of the porous metal support with an ink barrier layer comprising micron-sized particulate metal oxide and micron-sized particles comprising a second metal, a solvent, and a binder to form a green substrate composite; (b) heating the green substrate composite to form a porous metal substrate having pores in the pore size range of 3 μm to 75 μm and a porous metal support formed in a single layer while coating one side of the porous metal substrate with a barrier layer having micron-sized particles comprising a second metal and a micron-sized particulate metal oxide.
9. (a) the metal substrate of claim 1 comprising: (a)(i) a porous metal support forming a layer comprising a first metal having pores in the pore size range of 3 μm to 75 μm; (a)(ii) a barrier layer coated on one side of the porous metal support and comprising micron-sized particles of a second metal and micron-sized particulates of a metal oxide; (b) an electrode layer provided on the barrier layer of the metal substrate.
10. 10. The metal supported electrode of claim 9, wherein the metal supported electrode is a fuel electrode, preferably a fuel electrode comprising nickel and yttria stabilized zirconia.
11. (a) the metal substrate of claim 1 comprising: (a)(i) a porous metal support comprising a first metal forming a layer having pores in the pore size range of 3 μm to 75 μm; (a)(ii) a barrier layer coated on one side of the porous metal support and comprising micron-sized particles of a second metal and micron-sized particulates of a metal oxide; (b) a first electrode layer disposed on the barrier layer of the metal substrate; (c) an electrolyte layer disposed on the first electrode layer; and (d) a second electrode layer disposed on the electrolyte layer and having an opposite polarity to the first electrode layer.
12. the porous metal support layer comprises a ferritic alloy containing more than 15 mole percent chromium, has a layer thickness in the range of 80 μm to 1,000 μm, and a porosity in the range of 25 volume percent to 50 volume percent; the barrier layer has a layer thickness in the range of 10 μm to 50 μm; The micron-particle second metal has a particle size in the range 2 μm to 20 μm; the second metal is selected from the group consisting of nickel, iron, cobalt, chromium, copper, manganese and mixtures thereof; Micron-type particulate metal oxides have a particle size in the range of 0.1 μm or more and less than 1 μm; 12. The metal support electrochemical cell of claim 11, wherein the metal oxide is selected from ceria or rare earth doped ceria, lanthanum chromite or rare earth doped lanthanum chromite, or strontium titanate or rare earth doped strontium titanate.
13. the first electrode is a fuel electrode comprising a combination of a metal oxide selected from the group consisting of zirconium, yttrium, cerium, scandium, gadolinium, samarium, calcium, lanthanum, strontium, magnesium, gallium, barium oxides and mixtures thereof, and nickel or nickel oxide, the preferred fuel electrode being nickel oxide-yttria stabilized zirconia (NiO-YSZ); and / or the electrolyte comprises a metal oxide selected from the group consisting of oxides of zirconium, yttrium, cerium, scandium, gadolinium, samarium, lanthanum, strontium, magnesium, gallium, barium, calcium and mixtures thereof, with preferred electrolytes being yttria-stabilized zirconia or scandia-stabilized zirconia; and / or The second electrode has a composition formula ABO, where A is an element selected from the group consisting of barium, strontium, lanthanum, samarium, praseodymium, or a combination thereof, B is an element selected from the group consisting of iron, cobalt, nickel, and manganese, and O is an oxygen element. 3 The oxygen electrode layer is preferably selected from ABO 3 is lanthanum strontium cobalt ferrite (LaSrCoFeO 3 12. The metal support electrochemical cell of claim 11, wherein
14. 12. The metal support electrochemical cell of claim 11 which is a solid oxide fuel cell or a solid oxide electrolysis cell.
15. 12. The metal support electrochemical cell of claim 11, wherein the second electrode is an oxygen electrode and an intermediate layer having a layer thickness of 1 μm to 20 μm is disposed between the oxygen electrode and the electrolyte.